EXPERIENCE OF THE SYSTEM ORGANIZATION OF THE TRAINING OF FUTURE ENGINEERS IN THE CONDITIONS OF THE EDUCATIONAL AND INFORMATION ENVIRONMENT OF THE TECHNICAL UNIVERSITY - Rakhmanov, Vitalii (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article presents the experience of the systematic organization of the training of future engineers at the technical university. The systematic organization of training allows for the comprehensive structure of the educational process as an integral part based on the coordination of all elements of the educational and informational environment as an open synergistic system. The purpose of the article is to implement the experience of the systematic organization of training future specialists of a technical profile in solving educational tasks in professional activity. The introduction of creative teaching methods, the transition to a creative level of training, and the involvement of the educational and informational environment are the basis of the innovative educational process. The task of the research is to reveal the experience of using the system organization of training future engineers. Important in this process are interdisciplinary and multidisciplinary programs that are focused on solving complex professionally-oriented problems. Research methods consist in the study and generalization of domestic and foreign experience for the formation of conceptual provisions for the training of future engineers in the conditions of an educational and informational environment, scientific analysis, as well as observation of the educational process. The results. The essence of the implementation of the experience of the system organization of training future engineers is that the relatively independent components of the educational process are not considered in isolation, but in their relationship with the structural elements of the system. This makes it possible to identify integrative properties and qualitative features of the educational process for the formation of competencies of future specialists. The application of the experience of the system organization of the training of future engineers allows us to identify such a variable component of scientific knowledge, which is inherent in the components, namely: purpose, integrity, connection, structure, organization, levels of the system, their hierarchy, management, behavior, self-organization, its functioning and development . Conclusion. The experience of the systematic organization of the training of future engineers helps in implementing the principle of unity of pedagogical theory, experiment and practice. Pedagogical practice is an effective criterion for the truth of scientific knowledge, provisions that are developed by theory and verified by experiment. Practice becomes the source of new fundamental problems of education. Theory provides a basis for correct practical solutions, but global problems, tasks that exist in educational practice, generate new questions and require fundamental research